MANGROVE FOR FUTURE: GERAKAN PENANAMAN MANGROVE SEBAGAI SOLUSI PELESTARIAN PESISIR DI PULAU HARAPAN - Supriatiningsih, Supriatiningsih; Febrianti, Wenty; Rizaldy, M. Asmi; Ibrahim, Luckman; Kaunang, Sandra DE; Ruseno, Ndaru; Abdulah, Budiman; Suryaningsih, Maria; Ramdany, Ramdany; Ghofir, Ade; Maftuchah, Viniyati; Darwis, Hidayat; Rizal, Moch; Santoso, Imam; Suhana, Suhana; Susilawati, Susi; Mulyanti, Rita Yuni; Mahroji, Dwi (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2026)
Coastal areas face various environmental pressures, such as abrasion, ecosystem degradation, and reduced mangrove vegetation cover due to human activities and environmental change. Harapan Island, in the Seribu Islands, is one of the coastal areas with a vital mangrove ecosystem, both as a natural coastal barrier and as a habitat for marine life. However, the condition of the mangroves in this area still requires strengthening through conservation and rehabilitation activities involving the community. The